Lamb's Tales from Shakespeare: Script A - James F. Michael (Egypt New Horizon, 2005)
The Book Contains the Following Tales: . the Tempest Macbeth the Merchant of Venice a Midsummer Night's Dream Twelfth Night as You Like It
6 Items
Charles Lamb and Mary Lamb
Keywords: Literature (3GdCOHs; General